Benign Hydrothermal Synthesis of N‐doped TiO2 and TiO2‐CoS Nanostructures for Enhanced Visible‐Light Driven Photocatalytic Activity. Issue 43 (26th November 2019) - Dey, Kamol; Ganguli, Sumon; Alam, M. S.
Abstract: An efficient utilization of broad‐spectrum solar light to harvest energy for photocatalysis in a sustainable manner remains a critical challenge in the area of environmental remediation for a long time. To address this challenge, N‐doped TiO2 ‐CoS nanocomposite was successfully synthesized for the first‐time via a benign hydrothermal treatment adopting combination of doping, dimensional diversity and coupling strategies. The phase composition, surface morphology, nitrogen adsorption‐desorption analysis and photocatalytic degradation of Rhodamine B dye (RhB) in aqueous solution under simulated sunlight were well characterized and analyzed. The powder X‐ray diffraction patterns demonstrated the crystalline anatase phase of TiO2 in all photocatalysts. Scanning electron microscopy confirmed the formation of N‐doped TiO2 nanofibrous (NTNF) structure without phase alteration of TiO2 and demonstrated the co‐existence of spherical CoS particles that were randomly wrapped within the NTNF fibrous structure making the NTNF‐CoS nanocomposite. Nitrogen adsorption‐desorption analysis revealed higher specific surface area and larger pore volume of NTNF with mesoporous structure compared to those of N‐doped TiO2 nanoparticle (NTNP). The NTNF‐CoS nanocomposite showed superior photocatalytic degradation of RhB under visible light, which was predominantly ascribed to the synergistic effects of enhanced surface area, narrower band gap and efficient separation of photogenerated charge carriers. Thus, the NTNF‐CoS nanocomposite could be considered as a potential candidate for the removal or degradation of micro‐pollutant from the wastewater. Abstract : Nitrogen‐doped TiO2 nanofiber (NTNF) was coupled with CoS nanoparticle for fabricating NTNF‐CoS nanocomposite ‐ for the first‐time ‐ by mild hydrothermal method exploiting doping, dimensional diversity and coupling strategies to address environmental challenges. The proposed nanocomposite showed enhanced photodegradation of Rhodamine B dye under simulated sunlight which might be a cocktail effect of efficient light harvesting, accelerated surface reactions and promoted charge separation and transport.